Website defense strategy selection method based on attack-defense game and Monte Carlo simulation - Hao WU; Jiulun FAN; Chengzhe LAI; Jianhua LIU (Tongxin xuebao)
Aiming at the selection of security defense strategy in network attack-defense,the dynamic change process of mutual influence between attack-defense strategy was studied.Based on the game process of both offense and defense,the attack-defense game model was constructed,the attack process of the attacker based on Monte Carlo simulation was simulated and the attacker’s best attack utility was obtained,so as to calculate the best defensive utility of the defender.In order to maximize the effectiveness of network security defense,the optimal defense strategy under limited resources was implemented.Simulation experiments verify the effectiveness of the proposed method and analyze the influence of different parameter settings on the selection of defense strategy.